Exploring the construction of masculinity among male K-POP fans: a case study of K-POP fandom in Makassar City within the context of social environmet and education - Marhami, Ikhlasy Anugrah (Asian Journal Collaboration of Social Environmental and Education, 2024)
Background: In contemporary Indonesian society, K-Pop has emerged as a significant cultural phenomenon with a unique impact on gender perceptions. This study aims to explore the social construction of masculinity among K-Pop fanboys in Makassar, Indonesia, and examine the societal positioning of this form of masculinity. It draws on the definition of masculinity as a societal construct and examines how masculinity is shaped by social influences. Method: Utilizing Peter L. Berger and Thomas Luckmann's theory of social construction, the study views masculinity as a dynamic process involving externalization, objectivation, and internalization. It also references Janet Saltzman Chafetz's identification of areas of masculinity and R.W. Connell's concept of hegemonic masculinity to understand the hierarchical nature of masculine identities. Findings: Despite the popularity of K-Pop, male fans often face negative stigma and discrimination due to perceptions of K-Pop as feminine. The study reveals how masculinity is constructed among K-Pop fanboys in Makassar and their experiences of societal discrimination. Conclusion: By analyzing these dynamics, the study contributes to a broader understanding of the diverse forms of masculinity and the impact of cultural phenomena like K-Pop on gender constructs.  Novelty/Originality of this study:  This study highlights the unique dynamics in the construction of masculinity among male K-Pop fans in Indonesia, revealing the complex interactions between global culture, local gender identities, and social stigma. By applying social construction theory to the K-Pop phenomenon, this study opens up new perspectives in understanding the evolution of masculinity in the era of pop culture globalization.